PERBEDAAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DENGAN MODEL MIND MAPPING (PETA PIKIRAN) PADA MUATAN PELAJARAN BAHASA INDONESIA TEMA UDARA BERSIH BAGI KESEHATAN KELAS V SEMESTER I DI SD ISLAM AL-ABROR KECAMA - Anis Dwi Cahyati; Syarif Ibnu Rusdi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2017)
This study intended to know the difference of student learning outcomes with cooperative model type of Numbered Heads Together on Indonesian Language Studies Theme of Clean Air For Health in Fifth Grade Class at First Semester in Al-Abror Islamic Centre Elementary School Situbondo Distric, Situbondo Regency Month of Years 2017/ 2018. This study is using kind of quasi experimental. This sample of study is using purposive sampling technique by making certain considerations, with special selection or compared two homogeneous sample. This sample in this study as a control class is all students of fifth B grade class in Al-Abror Islamic Centre Elementary School, as many as 25 kids, and as an experimentaly class is all students of fifth C grade class in Al-Abror Islamic Centre Elementary School. The instrument is used a test instrument on the form of multiple choice. Instrument validity test is using point biseral formulas and instrument reability with Kuder-Richardson formulas. Prerequisite analysis test is data normality test with lilliefors test and homogeneity test with fisher test and data analysis with t-separated varians formulas. From the data analysis result obtained result thitung > ttabel (with level of significance 0,05 and df=48), that is 2,161 > 2,011. So, from the calculation can be concluded that Ho can be rejected and Ha can be accepted. That is wich means some differences in student learning outcomes if use cooperative models Numbered Heads Together (NHT) type with Mind Mapping models on Indonesian language studies theme of clean air for healt in fifth grade class at first semester in Al-Abror Islamic Centre Elementary School Situbondo Distric, Situbondo Regency month of years 2017/ 2018